Perception of sexual harassment among female athletes participating in team sports in the Northern Cyprus - Erdaǧ, Deniz; Özeriç, Mehmet; Harmancı, Bingül (Frontiers in Psychology, 2025)
IntroductionGender inequality in sports manifests in various forms, including differences in treatment, expectations, and exposure to inappropriate behaviors. Female athletes often face subtle and overt forms of discrimination, particularly in relation to coach behavior and sexual harassment. Understanding how female athletes perceive and react to such behaviors is crucial for developing effective strategies to foster safer and more equitable sports environments. This study aims to examine the multidimensional nature of gender inequality in sports by exploring female athletes' perceptions of coach behavior, their reactions to sexual harassment, their ambivalent sexist tendencies, and their attitudes toward sexual harassment.MethodsThis research utilized a quantitative survey design. Data were collected through the Socio-Demographic Information Form, the Reactions to Sexual Harassment in Sports Scale, the Ambivalent Sexism Inventory, and the Attitudes Toward Sexual Harassment Scale. The Coach Behavior List was also administered to assess athletes' perceptions of coach conduct. Participants included female athletes from various sports disciplines. Statistical analyses were performed to identify differences across age groups and sports disciplines.ResultsThe findings indicated no statistically significant differences in the total and subscale scores of the Coach Behavior List and the Reactions to Sexual Harassment in Sports Scale across different age groups. However, significant differences emerged across sports disciplines. Handball players reported lower scores on the sexual behaviors and non-instructional threatening behaviors subscales, suggesting reduced exposure to these forms of coach misconduct. Additionally, football and basketball players demonstrated stronger emotional reactions to sexual harassment compared to handball players. These patterns indicate variability in gender dynamics and exposure to harassment across different sports.Discussion and conclusionThe results highlight how gender inequality in sports is shaped not only by individual factors but also by the cultural and structural norms of specific disciplines. The lower levels of reported misconduct among handball players may reflect differing power dynamics or gender norms within that sport. Conversely, the stronger emotional reactions observed among football and basketball players suggest heightened sensitivity or exposure to harassment. These findings emphasize the need for multilayered interventions aimed at raising awareness, empowering female athletes, and addressing sexual harassment through prevention and education initiatives. Creating safer and more inclusive environments in sports requires both institutional reforms and cultural change.